2021
DOI: 10.1186/s12920-021-00974-3
|View full text |Cite
|
Sign up to set email alerts
|

EARN: an ensemble machine learning algorithm to predict driver genes in metastatic breast cancer

Abstract: Background Today, there are a lot of markers on the prognosis and diagnosis of complex diseases such as primary breast cancer. However, our understanding of the drivers that influence cancer aggression is limited. Methods In this work, we study somatic mutation data consists of 450 metastatic breast tumor samples from cBio Cancer Genomics Portal. We use four software tools to extract features from this data. Then, an ensemble classifier (EC) learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…For example, the SVM is a nonlinear algorithm, RF works with a decision tree group of algorithms, and the ANN is a neural networks-based algorithm. Various researchers have used these techniques in numerous studies [37][38][39][40]. Likewise, we had also used these techniques to develop predictive algorithms like QSPpred [25], VIR-siRNApred [41], AVP-IC50Pred [42], anti-flavi [12] and many more.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the SVM is a nonlinear algorithm, RF works with a decision tree group of algorithms, and the ANN is a neural networks-based algorithm. Various researchers have used these techniques in numerous studies [37][38][39][40]. Likewise, we had also used these techniques to develop predictive algorithms like QSPpred [25], VIR-siRNApred [41], AVP-IC50Pred [42], anti-flavi [12] and many more.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that STAT5B ectopically expressed in MCF7 and T47D activates cell proliferation and anchorage-independent growth (Tang et al 2010). Another protein ERα-regulated protein from TGFα-EGFR is PLCB1 which was recently identified as a metastatic breast cancer driver gene (Mirsadeghi et al 2021). PLCB1 was also found to be overexpressed in MCF7 WWOX-silenced cells under estradiol treatment.…”
Section: Wwox and Tgfα And Tgfβmentioning
confidence: 92%
“…As the volume and complexity of gene expression data burgeon, ML offers a suite of algorithms capable of deciphering intricate patterns within the data [ 12 ]. Studies have utilized various ML approaches, such as decision trees (DT) [ 13 ], neural networks (NN) [ 14 ], support vector machines (SVM) [ 15 ], logistic regression (LR) [ 16 ], and random forests (RF) [ 17 ], alongside more recent innovations in deep learning (DL) [ 18 , 19 ] and ensemble learning [ 20 , 21 ] methods such as extreme gradient boosting (XGBoost) [ 5 ] and adaptive boosting (AdaBoost) [ 22 ], to identify significant biomarkers in BC.…”
Section: Literature Reviewmentioning
confidence: 99%